Performance of Triploid Pacific Oysters Crassostrea Gigas (Thunberg) Reared in High Carrying Capacity Ecosystem: Survival, Growth, and Proximate Biochemical Composition - Goulletquer, Philippe; Joly, Jean-pierre; Gerard, Andre; Le Gagneur, Eric; Moriceau, Jacques; Peignon, Jean-marie; Heurtebise, Serge; Phelipot, Pascal (ICES-CIEM Mariculture Committee 1993 / F:24, 1993)
Triploid oysters C. gigas were produced in 1990 by treating fertilized eggs with cytochalasin B. Triploids, treated diploids, and controls were deployed in early 1991 in a high carrying capacity ecosystem on the Eastern Coast of Normandy (France). A monthly monitoring in 1992 showed that triploid yielded significantly higher growth rate and biochemical composition. However, growth was more heterogeneous. No evidence was found for a bimodal distribution within triploid groups after a 26-month rearing cycle. Triploids showed retardation of gametogenesis. Carbohydrates content in triploid remained almost constant (40%) from June to September. Their survival rates were significantly lower than diploids, and treated diploids were found more sensitive to environmental conditions than controls. Therefore, method of induction should be improved to maximize triploidy rate. We recommend further field testings to assess triploid response to stressful environmental conditions, particularly in low carrying capacity ecosystem. Une production d'huîtres japonaises triploïdes C. gigas a été réalisée en 1990 par induction à la cytochalasine B d'oeufs fertilisés. Triploïdes, diploïdes réfractaires et une population témoin ont été mis en élevage au début 1991 sur la côte Est de Normandie (France). Le suivi mensuel a montré une meilleure croissance et composition biochimique des triploïdes avec cependant une plus forte hétérogénéité en taille. Un seul mode a été observé après 26 mois d'élevage. Les triploïdes montrent un retard de gamétogénèse et une teneur constante en sucres de juin à septembre. Les taux de survie sont plus faibles chez les triploïdes, et les diploïdes traités sont plus sensibles que les témoins aux conditions environnementales. La technique d'induction doit être améliorée et la résistance des triploïdes testée en conditions stressantes